Treatment outcomes and associated factors among patients with multidrug-resistant tuberculosis in Southwestern Oromia, Ethiopia: ten-year retrospective analysis - Zegeye Bonsa; Mulualem Tadesse; Eba Bekele; Gari Abeba; Endashaw Solomon; Mohammed Husen; Getu Balay; Wakjira Kebede; Gemeda Abebe (BMC Infectious Diseases)
Abstract Background Treatment of rifampicin-resistant or multidrug-resistant tuberculosis (RR/MDR-TB) requires the use of second-line anti-TB drugs, which are less effective and more toxic. This study assessed treatment outcomes and factors associated with unfavorable treatment outcomes among RR/MDR-TB patients in Southwestern Oromia, Ethiopia. Methods A multicenter retrospective study was conducted on 226 RR/MDR-TB patients (six extrapulmonary and 220 pulmonary) treated under a national TB program between 2013 and 2022 at five treatment facilities in Southwestern Oromia, Ethiopia. RR/MDR-TB patient data, such as sociodemographic, clinical, and laboratory results and treatment outcomes, were collected from the RR/MDR-TB registry using a standard data extraction form between April and June 2023. Logistic regression analysis was used to explore the associations between risk factors and unfavorable treatment outcomes. Results Among 220 pulmonary RR/MDR-TB patients, 181 (82.3%) achieved favorable treatment outcomes (161 cured and 20 treatment completed). However, 39 (17.7%) patients had unfavorable treatment outcomes (12 were lost to follow-up, seven experienced treatment failure, and 20 died). Of the six extrapulmonary RR/MDR-TB patients, five (83.3%) had favorable treatment outcomes, and one (16.7%) was lost to follow-up. Pulmonary RR/MDR-TB patients with HIV infection (AOR = 4.85, 95% CI: 1.90 to 12.39), history of previous TB treatment (AOR = 3.09, 95% CI: 1.21 to 7.86), and low baseline BMI (AOR = 2.86, 95% CI: 1.06 to 7.72) had increased risk of unfavorable treatment outcomes. Conclusion Although the majority of RR/MDR-TB patients have favorable treatment outcomes, a significant proportion of patients still experienced unfavorable outcomes. Patients with HIV infection, history of previous TB treatment, and low baseline BMI require special attention to improve pulmonary RR/MDR-TB treatment outcomes. Future studies with larger sample sizes are required to evaluate treatment outcomes and associated factors among patients with extrapulmonary RR/MDR-TB.